How do you find an equation of the tangent line to the curve at the given point #y=3arccos(x/2) # and #(1,pi)#?

Answer 1

#y=-sqrt3*x+sqrt3+pi#

From the given curve #y=3*arccos(x/2)# and point #(1, pi)#

Find the first derivative by the formula

#d/dx(arccos u)=(-1)/sqrt(1-u^2)*d/dx(u)#
#(dy)/dx=d/dx(3*arccos(x/2))=3*(-1)/sqrt(1-(x/2)^2)*d/dx(x/2)#
#(dy)/dx=-3/(1/2*sqrt(4-x^2))*(1/2)#
at #x=1#
#(dy)/dx=-3/(1/2*sqrt(4-1^2))*(1/2)#
#(dy)/dx=-3/sqrt3=-sqrt3""""" "the" "slope"#

The Tangent line:

By using point-slope formula with slope #m=-sqrt3# and given point #(x_1, y_1)=(1, pi)#
#y-y_1=m*(x-x_1)#
#y-pi=-sqrt3*(x-1)#
#y=-sqrt3*x+sqrt3+pi#

I hope the explanation is useful...God bless..

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the equation of the tangent line to the curve y = 3arccos(x/2) at the point (1, π), we need to find the derivative of the function and evaluate it at x = 1.

The derivative of y = 3arccos(x/2) can be found using the chain rule.

dy/dx = 3 * d(arccos(x/2))/dx

To find d(arccos(x/2))/dx, we differentiate arccos(x/2) with respect to x.

d(arccos(x/2))/dx = -1 / sqrt(1 - (x/2)^2)

Substituting this back into the derivative equation, we have:

dy/dx = 3 * (-1 / sqrt(1 - (x/2)^2))

Now, we can evaluate dy/dx at x = 1:

dy/dx = 3 * (-1 / sqrt(1 - (1/2)^2)) = 3 * (-1 / sqrt(1 - 1/4)) = 3 * (-1 / sqrt(3/4)) = -4 / sqrt(3)

So, the slope of the tangent line at x = 1 is -4 / sqrt(3).

Using the point-slope form of a line, we can write the equation of the tangent line:

y - π = (-4 / sqrt(3))(x - 1)

Simplifying this equation, we get:

y = (-4 / sqrt(3))(x - 1) + π

Therefore, the equation of the tangent line to the curve y = 3arccos(x/2) at the point (1, π) is y = (-4 / sqrt(3))(x - 1) + π.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the equation of the tangent line to the curve ( y = 3\arccos\left(\frac{x}{2}\right) ) at the point ( (1, \pi) ), follow these steps:

  1. Find the derivative of the function ( y = 3\arccos\left(\frac{x}{2}\right) ) with respect to ( x ).
  2. Evaluate the derivative at the given point ( x = 1 ) to find the slope of the tangent line.
  3. Use the point-slope form of the equation of a line to find the equation of the tangent line.

First, find the derivative ( \frac{dy}{dx} ) of the function ( y = 3\arccos\left(\frac{x}{2}\right) ):

[ \frac{dy}{dx} = \frac{d}{dx}\left[3\arccos\left(\frac{x}{2}\right)\right] ]

Apply the chain rule:

[ \frac{dy}{dx} = 3\left(\frac{d}{du}\arccos(u)\right)\left(\frac{d}{dx}\frac{x}{2}\right) ]

[ \frac{dy}{dx} = 3\left(-\frac{1}{\sqrt{1-u^2}}\right)\left(\frac{1}{2}\right) ]

[ \frac{dy}{dx} = -\frac{3}{2\sqrt{1-\left(\frac{x}{2}\right)^2}} ]

Now, evaluate the derivative at ( x = 1 ) to find the slope of the tangent line:

[ \left.\frac{dy}{dx}\right|_{x=1} = -\frac{3}{2\sqrt{1-\left(\frac{1}{2}\right)^2}} ]

[ \left.\frac{dy}{dx}\right|_{x=1} = -\frac{3}{2\sqrt{1-\frac{1}{4}}} ]

[ \left.\frac{dy}{dx}\right|_{x=1} = -\frac{3}{2\sqrt{\frac{3}{4}}} ]

[ \left.\frac{dy}{dx}\right|_{x=1} = -\frac{3}{2\sqrt{\frac{3}{4}}} = -\frac{3}{2}\cdot\frac{2}{\sqrt{3}} = -\frac{3\sqrt{3}}{3} = -\sqrt{3} ]

Now that we have the slope of the tangent line, which is ( -\sqrt{3} ), and the point ( (1, \pi) ), we can use the point-slope form of the equation of a line:

[ y - y_1 = m(x - x_1) ]

[ y - \pi = -\sqrt{3}(x - 1) ]

[ y - \pi = -\sqrt{3}x + \sqrt{3} ]

[ y = -\sqrt{3}x + \sqrt{3} + \pi ]

Therefore, the equation of the tangent line to the curve ( y = 3\arccos\left(\frac{x}{2}\right) ) at the point ( (1, \pi) ) is ( y = -\sqrt{3}x + \sqrt{3} + \pi ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7